(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Data on the establishment of Citrostichus phyllocnistoides (Narayanan) in Sicily are reported. These Eulophid wasp was over 1999 introduced for strengthning the natural contro! of Phyllocnistis citrella Stainton.